Effectiveness of the PElEO program to develop the entrepreneurial potential of spanish students in secondary education and vocational training - Martín-Gutiérrez, Ángela; Fernández-Salinero Miguel, Carolina; García Mora, María Elena; Montero Pedrera, Ana María (Social Sciences & Humanities Open, 2025)
The general aim of the investigation was to determine the effectiveness of the PElEO program (educational program for the development of entrepreneurial potential in adolescents) in Spanish students (males and females). It was carried out with a pre-test and post-test design in a sample divided into a control group and an experimental group of students registered in the educational stages of Secondary Education and Vocational Training in order to test the hypotheses related to participation in the PElEO program and its effectiveness in formative dimensions considered. The program was effective and promoted the development of entrepreneurial potential and each of its five dimensions (Creativity, Personal Control, Goal Orientation, Leadership and Intuition for Problem Solving) in the group of individuals who participated. However, its impact was more pronounced among men than women, revealing potential entrepreneurial dimensions already present in women, establishing the bases for future entrepreneurial education proposals, and building upon those delineated in the European model Entrecomp. The originality of this study lies in the combination of three elements: 1) the analysed concept (entrepreneurial potential) and the terms associated with it; 2) entrepreneurship education in Spain currently conceived as the means for its development; and 3) the design, implementation, and analysis of the results of an entrepreneurship education program (PElEO), which provides relevant data about the differences between women and men.
Keywords: entrepreneurial potential; entrepreneurial education; spanish entrepreneurial education; PElEO educational program; entrepreneurship